Anxiety in oral presentation among engineering and non-engineering students in english language classrooms - Ibrahim, Hairunnisa (2019)
Oral presentations are one of the most common tasks given in university especially for undergraduate’s students in English as a second language classes. Students in all fields desire to disseminate the new knowledge they produce, and this is often accomplished by delivering oral presentations in class or in public lectures. Therefore, learning to deliver effective presentations is a necessary skill to master both for college and further endeavors. Fear or anxiety in the oral presentation can prevent you from taking risks to share your ideas, to speak about your work, and to present solutions to problems that affect many people, and as a result, it can affect how much you grow personally and professionally. At the same time, any negative public speaking experiences will make it less likely that you will speak in public in the future because fear teaches you to protect yourself from risky situations. The purpose of this study is to investigate the comparison of the anxiety-related problem between engineering and non-engineering students during their oral presentation. There were 120 students of two different faculties from a public university in Johor who participated in this study. Alongside class observation on student’s oral presentation in class, qualitative approaches using structured interviews were done over selected students and lecturers. The interviews were conducted between 5 students and 5 teachers to get clear evidence of anxiety occurrences during an oral presentation in the ESL classrooms. Based on the findings, there are no significant differences in the level of anxiety between engineering and non-engineering students. The major factors causing speaking anxiety during oral presentation in ESL classroom based on the overall analysis from the class observation show that both engineering and non engineering students have no proper eye contact with the audience, lack of knowledge of the target language, limited vocabulary repertoire, no appropriate body gestures, lack of stage presence, too nervous, stumble in the middle of presentation and low self confidence that leads to anxiety problem.